Miasta i ich obszary funkcjonalne w perspektywie badań politologicznych (Politeja, 2025)
CITIES AND THEIR FUNCTIONAL AREAS FROM THE PERSPECTIVE OF POLITICAL SCIENCE RESEARCHUrban studies within political science offer a lot in terms of enhancing understanding of the social and political processes taking place at every level of the local government. The author’s particular area of interest is the contribution of political studies to research on the functional areas of regional capital cities. Based on an analysis of contemporary city management concepts, the author points to compelling issues in the study of modern cities and their functional areas. At the same time, the author advocates for methodological pluralism, arguing that interdisciplinarity enables a better diagnosis of the specific nature of cities and their role in a changing world.